Latrophilins and Teneurins in Invertebrates: No Love for Each Other? - Schöneberg, Torsten; Prömel, Simone (Frontiers in Neuroscience, 2019)
Transsynaptic connections enabling cell–cell adhesion and cellular communication are a vital part of synapse formation, maintenance and function. A recently discovered interaction between the Adhesion GPCRs Latrophilins and the type II single transmembrane proteins Teneurins at mammalian synapses is vital for synapse formation and dendrite branching. While the understanding of the effects and the molecular interplay of this Latrophilin-Teneurin partnership is not entirely understood, its significance is highlighted by behavioral and neurological phenotypes in various animal models. As both groups of molecules, Latrophilins and Teneurins, are generally highly conserved, have overlapping expression and often similar functions across phyla, it can be speculated that this interaction, which has been proven essential in mammalian systems, also occurs in invertebrates to control shaping of synapses. Knowledge of the generality of this interaction is especially of interest due to its possible involvement in neuropathologies. Further, several invertebrates serve as model organisms for addressing various neurobiological research questions. So far, an interaction of Latrophilins and Teneurins has not been observed in invertebrates, but our knowledge on both groups of molecules is by far not complete. In this review, we give an overview on existing experimental evidence arguing for as well as against a potential Latrophilin-Teneurin interaction beyond mammals. By combining these insights with evolutionary aspects on each of the interaction partners we provide and discuss a comprehensive picture on the functions of both molecules in invertebrates and the likeliness of an evolutionary conservation of their interaction.